Amino acid‐based biostimulants and microbial biostimulants promote the growth, yield and resilience of strawberries in soilless glasshouse cultivation - Ruvini Ranasingha; Anya Perera; Kambiz Baghalian; Christos Gerofotis (Journal of Sustainable Agriculture and Environment, 2024)
Abstract Introduction The increasing demand for strawberries in the United Kingdom, valued for their flavour, nutrition and economic significance, presents challenges in maintaining consistent production, especially under various biotic and abiotic stress conditions. Traditional reliance on conventional agrochemicals to meet these demands is tempered by concerns about their health and environmental impacts, paving the way for eco‐friendly alternatives, such as biostimulants. However, their efficiency in commercial table‐top systems for June‐bearing and ever‐bearing strawberries under glasshouse conditions remains underexplored. Materials and methods This study investigated the efficiency of two commercial biostimulants in enhancing the growth, productivity and resilience of two strawberry varieties: ‘Malling Centenary’ (June‐bearer) and ‘Malling Ace’ (ever‐bearer) strawberry cultivars in a soilless hydroponic system within an unheated glasshouse. ‘Vitalnova Prime’ (VP), an amino acid and peptide‐based biostimulant derived from yeast, was applied every 2 weeks as a foliar spray (1 mL/L), whereas ‘Vitalnova Triboost’ (VT), a microbial inoculant with live cultures, was incorporated into the medium post‐transplanting (500 g/m3). Results VP significantly enhanced vegetative growth in both cultivars, resulting in substantial increases in number of leaves, crowns, crown diameter and shoot biomass accumulation compared to the control. VT also effectively improved multiple growth parameters compared to the control. Both biostimulants similarly improved crown formation and shoot dry weight in ‘Malling Centenary’. In terms of yield, both VP and VT increased yield in ‘Malling Ace’; notably, VP significantly enhanced the number of marketable fruits by 55% and average fruit weight by 56% compared to the control. Additionally, both biostimulants significantly reduced the occurrence of diseased fruits in both cultivars. Conclusion This study demonstrates that biostimulants significantly enhance the growth, yield, and resilience of strawberries in soilless cultivation systems within unheated glasshouses. These findings suggest that biostimulants offer a sustainable and promising approach to addressing the increasing global demand for high‐quality strawberries.